THE EFFECT OF EDUCATION ON IMPROVING PREGNANT WOMEN'S KNOWLEDGE ABOUT INTEGRATED ANC AT SADAR JAYA PUBLIC HEALTH CENTER, SIAK KECIL DISTRICT, BENGKALIS REGENCY - Shandra Yunita Nadeak; Wira Ekdeni; Rizka Mardiya; Fajar Sari Tanberika (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Maternal health services must meet the minimum frequency of pregnancy check-ups. In 2024, the coverage of ANC visits at the Sadar Jaya Community Health Center, Siak Kecil District, Bengkalis Regency, was 87.2% of the target of 90%. One of the contributing factors was the lack of implementation of an integrated ANC program for pregnant women. This study aims to determine the effect of education on increasing pregnant women's knowledge about integrated ANC. This study was a pre-experimental study. The population was all pregnant women in their first trimester in May 2026, totaling 40 people, with a sample size of 37 people.simple random sampling. Data analysis using t-test. The results of the study showed that the knowledge of pregnant women before education about integrated ANC was mostly (54.1%) with sufficient knowledge. The knowledge of pregnant women after education about integrated ANC was mostly (62.2%) with good knowledge. The effect of education on increasing the knowledge of pregnant women about integrated ANC with a ρ value of 0.000 < 0.05. Therefore, it is hoped that community health centers will improve knowledge and understanding, especially in providing services to pregnant women about integrated ANC.